2003
DOI: 10.1121/1.1570439
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of early reflections for speech in rooms

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
214
1
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(240 citation statements)
references
References 14 publications
16
214
1
9
Order By: Relevance
“…The results of Poissant et al ͑2006͒ suggest that signals comprised largely of early reflections may be less intelligible for implant users than signals comprised largely of direct arrivals. This hypothesis, if true, has important implications for implant users since recommendations for improving classroom acoustics often include increasing the level of early reflections ͑Siebein et al, 2000;Bradley et al, 2003͒. One simple way to evaluate this hypothesis is to compare intelligibility scores for speech received at small SLDs ͑hav-ing strong contributions from direct sound͒ with those for speech received at large SLDs ͑having strong contributions from reflected sound͒. Listeners with normal temporal integration abilities would be expected to recognize speech at the front and rear of the room with equal facility ͓assuming equal sound pressure levels ͑SPLs͔͒; listeners showing deficits in integration ability would be expected to show significant differences between the two locations.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Poissant et al ͑2006͒ suggest that signals comprised largely of early reflections may be less intelligible for implant users than signals comprised largely of direct arrivals. This hypothesis, if true, has important implications for implant users since recommendations for improving classroom acoustics often include increasing the level of early reflections ͑Siebein et al, 2000;Bradley et al, 2003͒. One simple way to evaluate this hypothesis is to compare intelligibility scores for speech received at small SLDs ͑hav-ing strong contributions from direct sound͒ with those for speech received at large SLDs ͑having strong contributions from reflected sound͒. Listeners with normal temporal integration abilities would be expected to recognize speech at the front and rear of the room with equal facility ͓assuming equal sound pressure levels ͑SPLs͔͒; listeners showing deficits in integration ability would be expected to show significant differences between the two locations.…”
Section: Introductionmentioning
confidence: 99%
“…Germane to this discussion are the findings of Bradley et al [23] indicating that for speech intelligibility-a crucial consideration for movies-it is the early reflections that are the main contributors. They concluded that early reflection energy arriving within about the first 50 ms following the direct sound has the same effect on speech intelligibility scores as an equal increase in the direct sound energy.…”
Section: Measures Of Room Reflectionsmentioning
confidence: 99%
“…These room models may not only have a short distance between the sound source and its surrounded walls but also sloped ceilings above the sound source.It can be generally concluded that the lower ceiling height above the sound source and shorter distance between the sound source and its surrounding walls may provide higher speech intelligibility in the most parts of the room because they will help to provide strong early sound energy reflections. However, if the room ceiling height is not adequate enough to distribute the early reflections to the rear room, speech intelligibility will be poor relative to the other parts of the room [20]. …”
Section: Simulation 1: Room Shape Vs Speech Intelligibilitymentioning
confidence: 99%